IMPLEMENTATION OF INCLUSIVE EDUCATION: OPPORTUNITIES AND BARRIERS IN THE LOCAL CONTEXT - Sutomo, Moh.; Lestari, Maghfirotul Firmaning; Ubaidillah, Sofwan Roif (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education aims to provide equal access to education for all students, including  those  with  special  needs,  in  a  friendly  and  supportive  learning environment. This study was conducted at SDS Ulul Albab, Jember Regency, with the aim of analyzing opportunities and barriers in the implementation of inclusive education in one particular local context. The research approach used was qualitative with a case study method. Data were collected through in-depth  interviews,  participant  observation,  and  document  analysis  from schools  that  implement  the  inclusive  education  model.  The  results  of  the study indicate that the main opportunities in the implementation of inclusive education  include  government  policy  support,  teacher  commitment,  and community  participation.  However,  significant  obstacles  were  also  found, such as the lack of facilities that support the needs of students with special needs, limited teacher competence, and the existence of social stigma against inclusive students. This study concludes that the implementation of inclusive education  requires  a  collaborative  approach  between  the  government, schools,  and  the  community  to  overcome  obstacles  and  maximize opportunities.  These  findings  provide  practical  recommendations  for stakeholders to improve the effectiveness of inclusive education at the local level.